Treatment of Multi-Focal Epilepsy With Resective Surgery Plus Responsive Neurostimulation (RNS): One Institution's Experience - Tran, Diem Kieu; Tran, Demi Chi; Mnatsakayan, Lilit; Lin, Jack; Hsu, Frank; Vadera, Sumeet (Frontiers in Neurology, 2020)
Objective: Patients with medically refractory focal epilepsy can be difficult to treat surgically, especially if invasive monitoring reveals multiple ictal onset zones. Possible therapeutic options may include resection, neurostimulation, laser ablation, or a combination of these surgical modalities. To date, no study has examined outcomes associated with resection plus responsive neurostimulation (RNS, Neuropace, Inc., Mountain View, CA) implantation and we describe our initial experience in patients with multifocal epilepsy undergoing this combination therapy. Methods: A total of 43 responsive neurostimulation (RNS) devices were implanted at UCI from 2015 to 2019. We retrospectively reviewed charts of patients from the same time period who underwent both resection and RNS implantation. Patients were required to have independent or multifocal onset, undergo resection and RNS implantation, and have a minimum of six-months for follow-up to be included in the study. Demographics, location of ictal onset, location of surgery, complications, and seizure outcome were collected. Results: Ten patients met inclusion criteria for the study, and seven underwent both procedures in the same setting. The average age was 36. All patients had multifocal ictal onset on video electroencephalogram or invasive EEG with four patients undergoing subdural grid placement and four patients undergoing bilateral sEEG prior to the definitive surgery. Five patients underwent resection plus ipsilateral RNS placement and the remainder underwent resection with contralateral RNS placement. Two minor complications were encountered in this group. At six months follow up, there was an average of 81% ± 9 reduction in seizures, while four patients experienced complete seizure freedom at 1 year. Conclusion: Patients with multifocal epilepsy can be treated with partial resection plus RNS. The complication rates are low with potential for worthwhile seizure reduction.